A new approach for the surgery of large renal masses: Abdominal wall flap incision - (:unkn) unknown (KARGER, 2006)
Introduction: The type of skin incision affects the course of surgery during radical nephrectomy. We investigated the efficacy of a new type of incision for the surgical approach to large renal masses. Patients and Methods: Fourty patients (23 males and 17 females, mean age 63 years) who underwent radical nephrectomy in our department between 2002 and 2004 were evaluated. The outcomes in the groups with chevron incision and abdominal wall flap incision (AFI) were compared in terms of greatest tumor diameter, operation duration, perioperative blood loss, postoperative complications, and duration of hospitalization. Statistical analysis was made by independent-samples t test. Results:Chevron incision was used in the first 15 patients, while subsequent 25 patients were operated via AFI. The operation duration was slightly longer in the AFI group (3.78 vs. 3 h); however, the mean largest tumor diameter was significantly greater in patients operated via AFI (11.3 vs. 7.4 cm, p < 0.05). The mean blood losses were 1,100 and 590 ml in the chevron incision and AFI groups, respectively (p < 0.05). There was no significant difference in terms of duration of hospitalization and postoperative morbidity. Conclusion: In our experience, AFI provides the best exposure and improved control of renal vessels and vena cava during radical nephrectomy and enables a safe dissection even in very large tumors with minimal blood loss. Copyright (c) 2006 S. Karger AG, Basel.
Keywords: abdominal wall flap incision; large renal masses, surgery; skin incision type; LAPAROSCOPIC RADICAL NEPHRECTOMY; CELL CARCINOMA; EXPERIENCE; COMPLICATIONS